2001
DOI: 10.1021/jm010256v
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Synthesis of d- and l-Cyclopentenyl Nucleosides and Their Antiviral Activity Against HIV and West Nile Virus

Abstract: Enantiomeric synthesis of D- and L-cyclopentenyl nucleosides and their antiviral activity against HIV and West Nile virus are described. The key intermediate (-)- and (+)-cyclopentenyl alcohols (7 and 15) were prepared from D-gamma-ribonolactone and D-ribose, respectively. Coupling of 7 with appropriately blocked purine and pyrimidine bases via the Mitsunobu reaction followed by deprotection afforded the target L-(+)-cyclopentenyl nucleosides (24-28, 31, 33, and 36). D-(-)-Cyclopentenyl nucleosides (1, 40, 43,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 36 publications
0
55
0
Order By: Relevance
“…Recent studies demonstrated that palmatine acts as a protease inhibitor of flavivirus whereas, ribavirin-5′-triphosphate and paclitaxel inhibited flavivirus NS3 protein-associated NTPase [30]. Neplanocin, another naturally occurring carbocyclic nucleoside, inhibits the flaviviral NS5 protein-associated methyltransferease [31]. Most alphavirus inhibitors, which inhibit virus replication, are nucleoside analogues e.g.…”
Section: Antiviral Activity Of Cphp and Capmentioning
confidence: 99%
“…Recent studies demonstrated that palmatine acts as a protease inhibitor of flavivirus whereas, ribavirin-5′-triphosphate and paclitaxel inhibited flavivirus NS3 protein-associated NTPase [30]. Neplanocin, another naturally occurring carbocyclic nucleoside, inhibits the flaviviral NS5 protein-associated methyltransferease [31]. Most alphavirus inhibitors, which inhibit virus replication, are nucleoside analogues e.g.…”
Section: Antiviral Activity Of Cphp and Capmentioning
confidence: 99%
“…For example, neplanocin A (Fig. 3), a naturally occurring carbocyclic nucleoside, and related abacavir and carbovir, in which the absence of a true glycosidic bond makes the compounds chemically more stable, as they are not susceptible to enzymatic cleavage by SAH hydrolase (Song et al, 2001). A further possibility to inhibit the interactions between cap-structure and its target protein, eucaryotic initiation factor 4E (eIF4E), is the reduction of the affinity of the last to the ligand.…”
Section: Enzyme Activities Associated With Ns3 and Ns5 Proteinsmentioning
confidence: 99%
“…However, ribavirin has been shown to be only weakly active in vitro against SARS-CoV, and to even enhance and prolong viral replication in mice (Barnard et al, 2006). Other agents such as isatine derivatives (Chen et al, 2005;Wu et al, 2005), small interfering RNA (Wu et al, 2005), glycyrrhizic acid derivatives (Hoever et al, 2005), peptide inhibitors (Wu et al, 2004;Zhang et al, 2006) and natural compounds like Chinese medical herb extracts (Xiao et al, 2003;Zhong et al, 2003;Li et al, 2005) The nucleoside analogues listed ( Figure 1) were synthesized as described elsewhere (Choo et al, 2006;Gadthula et al, 2005;Chen et al, 2004;Chun et al, 2000;Song et al, 2001;Chu et al, 1991;Liang et al, 1997;Sureyya et al, 2001 D-(4-8) and L-(9-13) (4) uracil (5) adenine (6) inosine (7) guanine (8) OH OH B = uracil (9) cytosine (10) adenine (11) inosine (12) guanine (13) B S B = thymine (14) cytosine (15) adenine (16) guanine ( (24) thymine (25) cytosine (26) B = 5-C1-uracil (27) thymine (28) cytosine (29) uracil (30) adenine ( The 3′-fluoro-2′,3′-dideoxy-2′,3′-didehydro-4′-ethynyl-D-and L-furanosyl nucleosides (21-26) Interestingly, …”
Section: Severe Acute Respiratory Syndrome (Sars) Is a New Form Of Nomentioning
confidence: 99%